Inconsistencies across repeated eyewitness interviews: supportive negative feedback can make witnesses change their memory reports - Henkel, Linda A. (Psychology, crime & law, 2017)
Past work shows that direct negative feedback and suggestive questioning can lead eyewitnesses to change their memory reports. Applying Gudjonsson’s [2003. The psychology of interrogations and confessions: A handbook. West Sussex: Wiley] model of interrogative suggestibility to interviews with witnesses, the present two experiments examined how indirect negative feedback delivered in a supportive manner from an interviewer can make witnesses change what they report they remember experiencing. After viewing a video of a crime, participants were interviewed twice, with either supportive negative feedback (i.e. with the interviewer sympathetically suggesting why many people’s memory may be inaccurate) or neutral feedback between the two rounds of questions. Results showed that people given supportive negative feedback changed significantly more of their responses than those given neutral feedback. Lower confidence ratings were associated with greater response change, but overall, despite having changed more responses, people given supportive negative feedback did not have reduced confidence or perceived accuracy. Type of feedback did not impact accuracy, and accuracy was not systematically related to confidence or perceived accuracy. Given the role that eyewitness reports play in the criminal justice system, better understanding factors that impact consistency and reliability is vital.